1982
DOI: 10.2134/agronj1982.00021962007400020003x
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control in Double Cropped Corn, Grain Sorghum, or Soybeans Minimum‐Till Planted Following Canning Peas1

Abstract: Double cropping involving minimum‐till planting has become popular in many parts of the USA. In Wisconsin, double‐cropping usually includes canning peas (Pisum sativum L.) as the spring crop. Trifluralin (a,a,a‐trifluoro‐2,6‐dinitro‐N,N‐dipropyl‐p‐toluidine) is used for weed control in much of this pea acreage. Since effects of trifluralin residues alone or in combination with subsequent herbicide treatments on summer crops and weeds were unknown, experiments were conducted at the Univ. of Wisconsin Arlington … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…EDUCED-and no-tillage soybean [Glycine max (L.) Merr.] production in wide rows (0.76-1.00 m) has been successful for full-season and double-crop soybean (Ndon et al, 1982;Tyler and Overton, 1982). Planting in rows less than 0.25 m wide (solid-seeding) is also becoming an acceptable farming practice with improvements in weed control methods and planting machinery (Wax and Pendleton, 1968;Wax et al 1977).…”
mentioning
confidence: 99%
“…EDUCED-and no-tillage soybean [Glycine max (L.) Merr.] production in wide rows (0.76-1.00 m) has been successful for full-season and double-crop soybean (Ndon et al, 1982;Tyler and Overton, 1982). Planting in rows less than 0.25 m wide (solid-seeding) is also becoming an acceptable farming practice with improvements in weed control methods and planting machinery (Wax and Pendleton, 1968;Wax et al 1977).…”
mentioning
confidence: 99%
“…A number of short-term studies (2-5 yr) have identified and stressed the importance of several doublecropping management variables such as timeliness of operations (12), tillage (1, 3,6,8,12,13,17,19,20,22), planting methods (12,22), row spacings (3,6,12), cultivar selection (4,12), fertilization (2,9,21), weed control (10,15,16,18,23), and residue management (1, 7,11,14,17,19). However, little is known about continuous long-term double-cropping and the potential for sustaining yields.…”
mentioning
confidence: 99%
“…Ndon et al (1982) demonstrated that, although weed growth late in the pea development phase was reduced, pea yields were not improved by use of trifluralin (a,a,a-trifluori-2,6- (Lynch and Mitchell 1953 As with IVDMD, the herbage of soybean was higher in N than any of the other crops (Tables 2 and 3). In agreement with these results, Okoli et al (1984) reported that soybean N concentration averaged 3.l4%o compared with only 1.44Vo in whole-plant corn.…”
mentioning
confidence: 99%